ETHICAL IN PROTECTING GENDER ISSUES AND FAMILY OPPRESSION AND VIOLENCE IN THE REPUBLIC OF UZBEKISTAN THE PLACE OF VALUES - Z. Ya. Rakhmonova (Journals Park Publishing, 2022)
In this article, the role of moral values in the protection of gender issues and oppression and violence in the family in the Republic of Uzbekistan, as well as the great work done to achieve gender equality in the years of independence, as well as the issues of social protection of the family, motherhood and childhood are emphasized.
Keywords: women's rights, girls and women, gender equality, family income, gender inequality, violence, social factors, equal rights, oppression.